Advances in Cancer Stem Cell Biology - Scatena, Roberto.; Scatena, Roberto.; Mordente, Alvaro.; Mordente, Alvaro.; Giardina, Bruno.; Giardina, Bruno. (Springer New York : Imprint: Springer, 2012)
Advances in Cancer Stem Cell Biology informs the reader about both basic and potential clinical applications of an intriguing subpopulation of cancer cells -defined in different way as cancer stem cells, cancer stem like cells, tumor maintaining cells and so on- which are deeply changing some fundamental aspects of molecular and clinical oncology. This text compiled by leading expert in the field, offers the readers a fundamental understanding about how these cells can contribute to a lot of intriguing and obscure aspects of cancer pathogenesis (i.e., cancer cell dormancy, chemoresistance, local and distant relapses). The Editors and contributing authors proficiently address the effects of cancer stem cells biological activities on the development and progression of cancer. While it remains true that there are no universal truths in cancer, Advances in Cancer Stem Cell Biology opens the discussion that pathophysiology of cancer can usually be associated with and significantly attributed to a particular subpopulation of cancer cells resembling in some molecular activities that of stem cells.